Development of diagnostic fragment ion library for glycated peptides of human serum albumin: targeted quantification in prediabetic, diabetic, and microalbuminuria plasma by parallel reaction monitoring, SWATH, and MSE - Korwar, Arvind M.; Vannuruswamy, Garikapati; Jagadeeshaprasad, Mashanipalya G.; Jayaramaiah, Ramesha H.; Bhat, Shweta; Regin, Bhaskaran S.; Ramaswamy, Sureshkumar; Giri, Ashok P.; Mohan, Viswanathan; Balasubramanyam, Muthuswamy; Kulkarni, Mahesh J. (Molecular & Cellular Proteomics, 2015)
Human serum albumin is one of the most abundant plasma proteins that readily undergoes glycation, thus glycated albumin has been suggested as an additional marker for monitoring glycemic status. Hitherto, only Amadori-modified peptides of albumin were quantified. In this study, we report the construction of fragment ion library for Amadori-modified lysine (AML), N(epsilon)-(carboxymethyl) lysine (CML)-, and N(epsilon)-(carboxyethyl) lysine (CEL)-modified peptides of the corresponding synthetically modified albumin using high resolution accurate mass spectrometry (HR/AM). The glycated peptides were manually inspected and validated for their modification. Further, the fragment ion library was used for quantification of glycated peptides of albumin in the context of diabetes. Targeted Sequential Window Acquisition of all THeoretical Mass Spectra (SWATH) analysis in pooled plasma samples of control, prediabetes, diabetes, and microalbuminuria, has led to identification and quantification of 13 glycated peptides comprised of four AML, seven CML, and two CEL modifications, representing nine lysine sites of albumin. Five lysine sites namely K549, K438, K490, K88, and K375, were observed to be highly sensitive for glycation modification as their respective m/z showed maximum fold change and had both AML and CML modifications. Thus, peptides involving these lysine sites could be potential novel markers to assess the degree of glycation in diabetes.

Detection of a target protein (GroEl2) in Mycobacterium tuberculosis using a derivative of 1,2,4-triazolethiols - Sarkar, Sampa; Swami, Sagar; Soni, Sarvesh Kumar; Holien, Jessica K.; Khan, Arshad; Korwar, Arvind M.; Likhite, Anjali P.; Joshi, Ramesh A.; Joshi, Rohini R.; Sarkar, Dhiman (Molecular Diversity, 2022)
Herein, we identified a potent lead compound RRA2, within a series of 54 derivatives of 1,2,4-triazolethiols (exhibit good potency as an anti-mycobacterial agents) against intracellular Mycobacterium tuberculosis (Mtb). Compound RRA2 showed significant mycobactericidal activity against active stage Mycobacterium bovis BCG and Mtb with minimum inhibitory concentration (MIC) values of 2.3 and 2.0 mu g/mL, respectively. At MIC value, RRA2 compound yielded 0.82 log reduction of colony-forming unit (cfu) against non-replicating Mtb. Furthermore, RRA2 compound was selected for further target identification due to the presence of alkyne group, showing higher selectivity index (> 66.66 +/- 0.22, in non-replicating stage). Using ``click'' chemistry, we synthesized the biotin linker-RRA2 conjugate, purified with HPLC method and confirmed the conjugation of biotin linker-RRA2 complex by HR-MS analysis. Furthermore, we successfully pulled down and identified a specific target protein GroEl2, from Mtb whole-cell extract. Furthermore, computational molecular modeling indicated RRA2 could interact with GroEl2, which explains the structure-activity relationship observed in this study.
Keywords: 1; 2; 4-triazolethiols; GroEl2; Mycobactericidal activity; Mycobacterium bovis BCG; Mycobacterium tuberculosis